Peranan Pembimbing Kamar Dalam Manajemen Kedisiplinan Santriwati Kelas 5 Tmi di Pondok Pesantren Al-Amanah Al-Gontory - Rabbi’ah, Fitrahtul; Mukti, Suheri; Kurniawan , M. (PT. Publikasiku Academic Solution, 2025)
This study aims to describe the role of room supervisors in the management of discipline of female students of class 5 TMI at Al-Amanah Al-Gontory Islamic Boarding School. The background of this study is the importance of discipline in the lives of students living in the boarding school environment, as well as the emergence of the room supervisor (murabbiyah) program as an effort to improve supervision and guidance of discipline. This study uses a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. The results of the study indicate that room supervisors have a role as supervisors, coaches, motivators, and mediators in maintaining and improving the discipline of female students. In addition, several obstacles were found in the implementation of these roles, such as time constraints, differences in the characters of female students, and minimal communication between supervisors and boarding school administrators. Nevertheless, various solutions have been implemented, such as personal approaches, consistent enforcement of rules, and cooperation with other parties in the boarding school environment. In conclusion, the role of room supervisors is very significant in shaping the disciplined character of female students and supporting the creation of a conducive dormitory environment.